The power of chiasmus: Exploring the prayer of Esther in LXX Esther - Beer, Sanrie M. de (HTS teologiese studies, 2023)
As a figure constitutional of meaning within texts and schemes of thought, chiasmus plays an essential role. Taking chiasmi beyond their purely stylistic role calls for exploring their structural and meaning-defining role within texts and systems of thought. This study endeavoured to investigate the chiastic structure(s) of LXX Esther’s Addition C, the Prayer of Esther. The reverse parallelism of chiasmus can symbolise a wide series of affiliations. Jamin Pelkey’s semiotic typology of chiasmus was utilised as a heuristic prism to explore the chiastic structure(s) referred to in LXX Esther’s Addition C (17k–z) and Addition D. A crucial question is in what ways and how these chiasmi contribute to communicate intersections or meeting points between two possibilities. Chiasmus can be employed both to outline contradictions or rifts between some set of oppositions and at the same time bring these differences into dialogue. It was illustrated how oppositions and contradictions related to the prayer of Esther are transcended.Contribution: Referring to the narrative of LXX Esther, this article contributed to contested historical thought, source interpretation and literary studies.